Credit Insurance - Pearce, Eric A. (Assurances, 1975)
Quite recently I wished to obtain details with regard to Credit Insurance and was surprised to find how little information has been published, in comparison with the abundance of books and other writings relative to many other classes of insurance. For example, the most recently published text book seems to have been written as long ago as 1957, by Hans Karrer of Zurich, under the title Elements of Credit Insurance. It has not been re-published or brought up to date. Nor so far as I could ascertain, are there Study Courses or Reports by Student Groups. These notes are based on the practices which pertain in England, but will, I think, be of interest to readers in other countries where similar insurance principles apply.